The Role of Working Capital Management in Increasing Profitability (A Study of Fashion Retail Companies Listed on the Indonesia Stock Exchange During and Post Covid-19) - Bil Huda, Muhammad Arsala; Layyinaturrobaniyah, Layyinaturrobaniyah (Dinasti Publisher, 2025)
Working capital management is a financial management aspect aimed at optimizing current assets and liabilities to enhance profitability with minimal operational costs. This study aims to analyze the impact of working capital management on profitability in four fashion retail companies listed on the Indonesia Stock Exchange. The method used in this study is panel data regression. The results show that Days Sales Inventory (DSI) positively affects the Gross Profit Margin (GPM) but negatively affects the Operating Profit Margin (OPM). Days Sales Outstanding (DSO) has a negative impact on both GPM and OPM, while Days Payable Outstanding (DPO) positively affects OPM but has no significant effect on GPM. Meanwhile, the Cash Conversion Cycle (CCC) negatively impacts GPM and has no significant effect on OPM. These findings provide valuable insights into working capital management to enhance profitability in fashion retail companies.